2015
DOI: 10.1016/j.watres.2015.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Heteroaggregation of engineered nanoparticles and kaolin clays in aqueous environments

Abstract: a b s t r a c tThe increasing and wide use of nanoparticles (NPs), including TiO 2 and Ag NPs, have raised concerns due to their potential toxicity and environmental impacts. Kaolin is a very common mineral in aquatic systems, and there is a very high probability that nanoparticles (NPs) will interact with these clay minerals. We studied the effect of kaolin particles on the aggregation of NPs under different conditions, including the role of pH, ionic strength (IS), and humic acid (HA). We show that kaolin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 136 publications
(57 citation statements)
references
References 47 publications
2
55
0
Order By: Relevance
“…Even though the measured surface charge is similar at pH 4 and pH 8, montmorillonite is much less stable at pH 4 (critical coagulation concentration (CCC) around 35 mM) than it is at pH 8 (CCC around 100 mM). In a recent study [97], we investigated the effect of kaolin particles on the aggregation of TiO 2 and Ag NPs under different conditions. We found that kaolin reduces the energy barrier and the CCC at pH 4, but it promotes NPs aggregation via heteroaggregation at pH 8.…”
Section: Heteroaggregation Between Nanoparticles and Natural Colloidsmentioning
confidence: 99%
“…Even though the measured surface charge is similar at pH 4 and pH 8, montmorillonite is much less stable at pH 4 (critical coagulation concentration (CCC) around 35 mM) than it is at pH 8 (CCC around 100 mM). In a recent study [97], we investigated the effect of kaolin particles on the aggregation of TiO 2 and Ag NPs under different conditions. We found that kaolin reduces the energy barrier and the CCC at pH 4, but it promotes NPs aggregation via heteroaggregation at pH 8.…”
Section: Heteroaggregation Between Nanoparticles and Natural Colloidsmentioning
confidence: 99%
“…To detect the dominant effect of CeO 2 and TiO 2 ENPs on heteroaggregation, the experiments were conducted by mixing CeO 2 and TiO 2 ENPs stock solution with different mass ratios (0.1/9.9, 1/9, 5/5, 9/1, 9.9/0.1), for a total concentration of 10 mg/L (Our preliminary study showed [26,52,58] that 10 mg/L ENPs could more clearly indicate the aggregation behavior even if it may be unable to represent low environment concentration of ENPs like ng/L or μg/L). 5 mmol/L NaCl was used to provide IS.…”
Section: Aggregation and Co-sedimentation Experimentsmentioning
confidence: 99%
“…Most heteroaggregation studies have used dynamic light scattering (DLS) and attachment efficiency for understanding these processes [14,26,27]. Dusak et al suggested that the mass ratios of multiwall carbon nanotubes (MCNTs) and hematite nanoparticles (Hem ENPs) (15 g/L) have influence on the heteroaggregation rates as measured by DLS and their zeta potential [28].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations